The diagnostic analysis of the fault coupling effects in planet bearing - Xue, S.; Wang, C.; Howard, Ian; Lian, P.; Chen, G.; Wang, Y.; Yan, Y.; Xu, Q.; Shi, Y.; Jia, Y.; Zheng, Y.; Wang, N. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
© 2019 Elsevier Ltd